1996
DOI: 10.1063/1.117212
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs metal-semiconductor-metal photodetectors with engineered Schottky barrier heights

Abstract: Articles you may be interested inModeling a backgated GaAs metal-semiconductor-metal photodetector

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…3 shows simulated relation between dark current and electron barrier height for our homoepitaxial ZnSe MSM photodetectors bias at 15 V. With such a large bias, we can ensure the regions between electrodes were fully depleted. It was found that measured dark currents were larger than the theoretical minimum [7]. In other words, Eq.…”
Section: Resultsmentioning
confidence: 80%
“…3 shows simulated relation between dark current and electron barrier height for our homoepitaxial ZnSe MSM photodetectors bias at 15 V. With such a large bias, we can ensure the regions between electrodes were fully depleted. It was found that measured dark currents were larger than the theoretical minimum [7]. In other words, Eq.…”
Section: Resultsmentioning
confidence: 80%
“…In this mode of operation, one of the electrodes is forward biased (anode) and the other is reverse biased (cathode). Moreover, both electron and hole barrier heights, Φ Bn and Φ Bp respectively, determine the dark current according to the equation [7] …”
Section: Resultsmentioning
confidence: 99%
“…Similar techniques were applied for InGaAs III-V and Si, Ge substrate MSM photodetectors as well [7,8]. The asymmetry MSM structure is implemented with different metals on anode and cathode as compared to the same metals on anode and cathode in conventional symmetry MSM one.…”
Section: Introductionmentioning
confidence: 98%
“…To reduce the dark current, we chose to work in the diffusion regime (V < V FB ) and to use a high contact barrier metal (Platinum). The typical dark current in our sample is around 10 nA at 20 V. To work in the full-depletion regime and still have a low dark current, we could use an asymmetrical junction [32,33] such as Platinum-Si-Chrome. The chrome potential barrier will strongly limit the hole current.…”
Section: Experimental Confirmation By Ebic Measurementsmentioning
confidence: 99%